Trends, risk factors, and outcomes of unplanned extubation in a neonatal intensive care unit: a seven-year retrospective study - Ali, Kamal; Almahdi, Mohammed; Algarni, Saleh S.; Alsaif, Saif; Alharbi, Reem O.; Alqahtani, Maisa A.; Aldubaian, Rashed; Alsharif, Malak; Castro, Mark; Esclanda, Abigail; Althubaiti, Manal; Alrahili, Mohanned; et al. (Frontiers in Pediatrics, 2025)
BackgroundUnplanned extubation (UE) is a critical adverse event in neonatal intensive care units (NICUs), contributing to increased morbidity, prolonged mechanical ventilation, and potential complications such as airway trauma, ventilator-associated pneumonia. This study aimed to evaluate the incidence and trends of UE over a seven-year period, identify associated risk factors, and assess clinical outcomes following these events.MethodsThis retrospective observational study was conducted at the NICU of King Abdulaziz Medical City, Riyadh, from January 2018 to December 2024. Data were extracted from electronic medical records and included demographic details, ventilation-related parameters, and clinical outcomes of neonates experiencing UE. UE events were defined as the unintentional removal of an endotracheal tube during mechanical ventilation. The primary outcome was the incidence of UE per 100 ventilator days. Trends in UE rates over the seven-year study period were analyzed using linear regression. Logistic regression analysis was performed to identify predictors of reintubation following UE.ResultsA total of 175 UE episodes were recorded over the study period. The annual UE rate ranged from 1.31 per 100 ventilator days in 2021 to the lowest recorded rate of 0.42 in 2024, demonstrating an overall decline. Notably, the lowest UE rate was observed in 2024, despite the highest number of ventilator days and an increase in unit capacity, coinciding with improved respiratory therapist (RT) staffing levels. Reintubation was required in 52% of cases, with 81% of those reintubated requiring immediate intervention. Lower gestational age (GA) was associated with increased odds of reintubation (OR = 0.79, 95% CI: 0.66–0.93, p = 0.006), as was lower birth weight (OR = 1.002, 95% CI: 1.001–1.003, p = 0.002). HFOV use at the time of UE was linked to a higher reintubation rate (p < 0.001). Duration of ventilation and length of hospital stay were significantly longer in infants who required reintubation after UE (p < 0.001, 0.004 respectively). Mortality prior to discharge was notably higher among neonates who required reintubation (23%) compared to those who did not (3%, p < 0.001). Linear regression analysis demonstrated no statistically significant trend in UE rates over the seven-year study period (p = 0.206).ConclusionsThe study demonstrated an overall decline in UE rates over the seven-year period, with the lowest rate observed in 2024. This decline occurred despite the highest number of ventilator days and increased NICU capacity, suggesting that improvements in workforce staffing, particularly an increase in respiratory therapist coverage, contributed to enhanced patient safety. Reintubation following UE was influenced by gestational age, birth weight, and pre-extubation FiO₂ levels, emphasizing the need for improved preventive strategies. Efforts to minimize UE, including enhanced tube securement, optimization of sedation practices, and adherence to standardized care protocols, are essential for reducing associated risks and improving neonatal outcomes.